Cholesterol: A Gatekeeper of Male Fertility? - Sèdes, Lauriane; Thirouard, Laura; Maqdasy, Salwan; Garcia, Manon; Caira, Françoise; Lobaccaro, Jean-Marc A.; Beaudoin, Claude; Volle, David H. (Frontiers in Endocrinology, 2018)
Cholesterol is essential for mammalian cell functions and integrity. It is an important structural component maintaining the permeability and fluidity of the cell membrane. The balance between synthesis and catabolism of cholesterol should be tightly regulated to ensure normal cellular processes. Male reproductive function has been demonstrated to be dependent on cholesterol homeostasis. Here we review data highlighting the impacts of cholesterol homeostasis on male fertility and the molecular mechanisms implicated through the signaling pathways of some nuclear receptors.